KARAKTERISTIK TEKNIS BETON DAN MORTAR MENGGUNAKAN PASIR BONDO HITAM DAN BONDO MERAH - Pagut, Adhytius H.; Karels, Dolly W.; Hunggurami, Elia (Jurnal Teknik Sipil, 2017)
Constructions in East Manggarai and Manggarai use the dunes as fine aggregate material in the manufacture of concrete and mortar. However the properties and characteristic of the sand is scientifically unknown, so it is necessary to do research on the study of the sandstechnical characteristics of concrete and mortar. The constructed by the quality plan: 17.5 MPa, 22.5 MPa, 30 MPa, while the mortar cube was constructed with variation of mix as follows 1Pcc:2Psr, 1Pcc:4Psr, 1Pcc:6Psr, 1Pcc:8Psr. The concrete strength test results demonstrate that the compressive strength of concrete using Bondo black and red sand ishigher for all quality of planned concrete, with the compressive strength as follows 19.08 MPa, 23.38 MPa, 31.65 MPa, 19.87 MPa, 24.91 MPa,32.10 MPa, compared to the concrete using Takari sand with the compressive strength only reached 18.74 MPa, 23.04 MPa, 31.14 MPa. Compressive strength test of mortar using Bondo black and red sand showed a higher strength with the compressive strength respectively as follows 33.44 MPa, 28.64 MPa, 25.20 MPa, 12.80 MPa, 34.32 MPa, 29.60 MPa, 26.24 MPa, 13.68 MPa, compared to the mortar using Takari sand which only reached 31.68 MPa, 28.08 MPa, 23.44 MPa, 10.96 MPa.